The application of prophylactic balloon occlusion of the internal iliac artery for the treatment of placenta accreta spectrum with placenta previa: a retrospective case-control study - Ying Peng; Lai Jiang; Cheng Peng; Dabao Wu; Ling Chen (BMC, 2020)
Abstract Background Severe obstetric haemorrhage caused by placenta accreta spectrum (PAS) results in significant maternal morbidity and mortality. The effectiveness of prophylactic balloon occlusion of the internal iliac artery in PAS patients remains controversial. Therefore, we conducted a retrospective case-control study to investigate the clinical effectiveness of this treatment. Methods The clinical data of 104 patients with PAS complicated with placenta previa who delivered by caesarean section between January 2016 and January 2019 were collected, and the patients were divided into two groups. The study group (48 cases) underwent internal iliac artery preset balloon occlusion before caesarean section and uterine artery embolisation according to the bleeding status after surgery, while the control group (56 cases) did not undergo internal iliac artery preset balloon occlusion before caesarean section. Results The operation and hospitalisation times in the study group were longer than those in the control group. Additionally, the hysterectomy rate in the study group was significantly higher than that in the control group. No significant differences in blood loss, blood transfusion volume, urinary system injury, postoperative ICU transfer rate, or neonatal scores were identified between the groups. Among the patients without invasive placenta (placenta increta and percreta), blood loss was lower in the study group, and the caesarean hysterectomy rate did not significantly differ between the groups. Among the patients with invasive placenta, blood loss and the caesarean hysterectomy rate did not significantly differ between the groups. The risk of hysterectomy in the study group was related to invasive placenta penetration, a large area of placental invasion, or abnormal vascular filling. One patient in the study group had a thrombus in the left lower extremity artery. Conclusions Balloon occlusion of the internal iliac artery is effective for haemostasis of placenta previa in the absence of invasive placenta. For patients with invasive placenta, especially placenta percreta, a large area of placental invasion or abnormal vascular filling suggests the need for hysterectomy. The risks of the prophylactic use of internal iliac artery balloon occlusion include vascular injury and thrombus formation.